Impact of removing prescription charges on health outcomes: protocol for a randomised controlled trial. Issue 7 (22nd July 2021) - Cousins, Kimberly; Norris, Pauline; Horsburgh, Simon; Smith, Alesha; Keown, Shirley; Samaranayaka, Ariyapala; Marra, Carlo; Churchward, Marianna
Abstract : Introduction: Prescription charges prevent many people from accessing the medicines they need to maintain or improve their health. In New Zealand, where most people pay $5 per prescription item, Māori and Pacific peoples, those living in most deprived areas and those with chronic health conditions are the most likely to report that cost prevents them from accessing medicines. Methods and analysis: This randomised controlled trial (RCT) will evaluate the effect of removing prescription charges on health outcomes and healthcare utilisation patterns of people with low income and high health needs. We will enrol 2000 participants: half will be allocated to the intervention group and we will pay for their prescription charges for 12 months. The other half will receive usual care. The primary outcome will be hospital bed-days. Secondary outcomes will be: all-cause and diabetes/mental health-specific hospitalisations, prescription medicines dispensed (number and type), deaths, emergency department visits and quality of life as measured by the 5-level EQ-5D version. Costs associated with these outcomes will be compared in an economic substudy. A qualitative substudy will also help understand the impact of free prescriptions on participant well-being using in-depth interviews. Discussion: Being unable to afford prescription medicines is only one of many factors that influence adherence to medicines, but removing prescription charges is relatively simple and in New Zealand would be cheap compared with other policy changes. This RCT will help identify the extent of the impact of a simple intervention to improve access to medicines on health outcomes and health service utilisation. Ethics and dissemination: This study was approved by the Central Health and Disability Ethics Committee (NZ) in July 2019 (19/CEN/33). Findings will be reported in peer-reviewed publications, as well as in professional newsletters, mainstream media and through public meetings. Trial registration number: ACTRN12618001486213p.